2017
DOI: 10.18632/oncotarget.14733
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, toxicity and anticancer activities of arsenic compounds

Abstract: A variety of studies indicated that inorganic arsenic and its methylated metabolites have paradoxical effects, namely, carcinogenic and anticancer effects. Epidemiological studies have shown that long term exposure to arsenic can increase the risk of cancers of lung, skin or bladder in man, which is probably associated with the arsenic metabolism. In fact, the enzymatic conversion of inorganic arsenic by Arsenic (+3 oxidation state) methyltransferase (AS3MT) to mono-and dimethylated arsenic species has long be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
129
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(133 citation statements)
references
References 174 publications
1
129
0
3
Order By: Relevance
“…Chronic arsenic exposure has become a worldwide public health problem. Humans are exposed to arsenic mainly through the ingestion of arsenic‐contaminated water, food, and air . The World Health Organization has set the arsenic standard for drinking water at 10 µg/L.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic arsenic exposure has become a worldwide public health problem. Humans are exposed to arsenic mainly through the ingestion of arsenic‐contaminated water, food, and air . The World Health Organization has set the arsenic standard for drinking water at 10 µg/L.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization has set the arsenic standard for drinking water at 10 µg/L. Approximately, 200 million people in the world are at risk from the high concentrations (>10 µg/L) of arsenic in their drinking water . On the other hand, inorganic arsenic has long been used as medicine for some severe diseases in China and ancient Greece, and especially arsenic trioxide (ATO; As 2 O 3 ) has been recently identified as a remarkable therapeutic agent to treat acute promyelocytic leukemia (APL) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the arsenic biotransformation, a detoxification system that is present from bacteria to humans, first, the arsenate is converted into arsenite and then transformed into monomethylated, dimethylated, and trimethylated products . Thus, studies about the chemical form of arsenic, especially its transformation, allow to understand the biogeochemical cycling of this element in peculiar geo‐systems, and offer a molecular explanation of how exposed organisms tolerate arsenic in their environment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, organic arsenicals are generally thought to induce the apoptosis rather than cell re‐differentiation, which means organic arsenicals may carry out the anti‐cancer efficacy toward leukemia and lymphoma, as well as solid tumors. It has been reported that organic arsenical DAR can induce the cell cycle arrest, mitochondrial dysfunction, MAPK‐mediated SHP1‐dependent cell death or ROS‐mediated apoptosis . Although the signal pathways activated by DAR are diverse for the different cell lines, the influence on mitochondria is not neglected in all functional mechanisms.…”
Section: Introductionmentioning
confidence: 99%